A study of on-line information retrieval systems and their application in the Philippines - Santos, Alicia V. (Institute of Library Science, University of the Philippines Diliman, 1981)
This special problem aims to make a preliminary identification of on-line information retrieval systems in the Philippines, to briefly describe the data access and handling practices of the on-line systems and to contribute to a compilation of information on on-line systems in the hope that it will promote better utilization of available computer hardware and software especially in library applications and better cooperation and resource-sharing among the institutions in the Philippines.